Social information research - Widén, Gunilla; Holmberg, Kim (Library and information science (New York, N.Y.) ;, 2012)
Information we receive from and create together with our social networks is becoming increasingly important. Social information has a great impact on our information behaviour and there are many possible angles and layers in studying social aspects in information science. This book presents some of these angles. Social Information Research, co-edited by Gunilla Widen and Kim Holmberg communicates current research looking into different aspects of social information as part of information behaviour research. There is a special emphasis on the new innovations supporting contemporary information behavior and the social media context within which it can sit. As a concept, social information has been studied in biology, psychology and sociology among other disciplines. This book is relevant for various actors in the library and information science field and will be useful for researchers, educators, and practitioners while coordinating empirical research on social information and providing an overview of some of the present research about social information.